2014
DOI: 10.1002/ldr.2275
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Land Cover Changes in Eastern Tigray (Ethiopia) from 1965 to 2007: Are There Signs of a Forest Transition?

Abstract: This paper examines whether eastern Tigray is still in a phase of land degradation or if a trend of landscape greening has started. Hitherto, the land cover in five representative Tigray villages was mapped for three different periods: 1965, 1994, and 2007. These maps were based on the interpretation of aerial photographs and high‐resolution satellite imagery in combination with field validation. The results show a strong decrease of the forest and bush land in favor of arable land and rangeland from 1965 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 43 publications
3
88
0
Order By: Relevance
“…However, it is also known for its more recent experiences with soil and water conservation (SWC) activities (Alemayouh et al, 2009;Nyssen et al, 2010). Physical SWC structures (Alemayouh et al, 2009;Negusse et al, 2013) and biological SWC measures through plantation and enclosures (Descheemaeker et al, 2006(Descheemaeker et al, , 2008Belay et al, 2015) have been practised in the semi-arid parts of the basin. These interventions have been implemented at watershed level for the last three decades.…”
Section: Study Area Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also known for its more recent experiences with soil and water conservation (SWC) activities (Alemayouh et al, 2009;Nyssen et al, 2010). Physical SWC structures (Alemayouh et al, 2009;Negusse et al, 2013) and biological SWC measures through plantation and enclosures (Descheemaeker et al, 2006(Descheemaeker et al, , 2008Belay et al, 2015) have been practised in the semi-arid parts of the basin. These interventions have been implemented at watershed level for the last three decades.…”
Section: Study Area Descriptionsmentioning
confidence: 99%
“…Human interventions expressed in terms of water abstraction, implementation of large-scale soil and water conservation, deforestation, and afforestation in the upstream catchments are the more likely driving forces of changes in the flow regimes, rather than climatic conditions. For example, Nyssen et al (2005) and Belay et al (2015 reported that a strong decrease of forest and bushland has occurred in favour of cultivable and grazing lands from the 1960s to early 1990s. However, the rate of deforestation and land degradation in most parts of the basin has slowed down and even started to recover by increasing the coverage of vegetation from the late 1990s onwards (Nyssen et al, 2010).…”
Section: Drivers For Streamflow Variabilitiesmentioning
confidence: 99%
“…Several studies have analyzed land use change in the Tigray region (Meire et al 2012;Kassa 2013). Belay et al 2014 analyzed land use and land cover changes in Tigray from 1965 to 1994 and 2007. One of their findings is that between 2001 and 2009, areas of central and eastern Tigray, which saw significant investments in land and water management, were greener than what could be expected on the basis of rainfall.…”
Section: Outcomes and Impactsmentioning
confidence: 99%
“…The change of land use and cover in a certain range is the result of changes of various types of land use and cover types, and land use and cover as well as its variation and change rate can quantificationally reveal the overall level and change trend of land use and cover in the range (Yu et al, 2014;Belay et al, 2015). Variation and change rate of land use and cover can be expressed as…”
Section: Analysis Of Change Degree Of Land Use and Covermentioning
confidence: 99%